Proceedings of the 4th International Symposium on Health Research (ISHR 2019) 2020
DOI: 10.2991/ahsr.k.200215.118
|View full text |Cite
|
Sign up to set email alerts
|

Too Posh to Push: Determinants of Planned C-Section Delivery Among Indonesian Women

Abstract: Caesarean section (CS) delivery in Indonesia is on the rise and has drawn a considerable attention to its social determinants. However, information on planned CS delivery is limited in the Indonesian setting. Hence, this study aims at investigating its correlates. We employed data from the 2017 round of the Indonesian Demographic and Health Survey. The dependent variable is a nominal variable representing method of delivery (1 = natural, 2 = planned CS, 3 = unplanned CS). The explanatory variables comprise thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(39 reference statements)
0
3
0
Order By: Relevance
“… 13 29 There is a positive association between health insurance coverage and pre-labour planned C-section use in Indonesia. 31 Considering the recency of JKN implementation, this study did not have the opportunity to analyse the effect of insurance usage on C-section access.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 29 There is a positive association between health insurance coverage and pre-labour planned C-section use in Indonesia. 31 Considering the recency of JKN implementation, this study did not have the opportunity to analyse the effect of insurance usage on C-section access.…”
Section: Discussionmentioning
confidence: 99%
“…13 29 There is a positive association between health insurance coverage and pre-labour planned C-section use in Indonesia. 31 Considering the recency of JKN implementation, this study did not have the opportunity to analyse the effect of insurance usage on C-section access. Inconsistent with findings in other developing countries, Indonesian C-section rate by public services was higher than that by private services in 1998-2012.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in access to internet facilities, maternal age, and access to private insurance have increased the probability of planned C-sections among Indonesian women [45]. The current study revealed that ANC utilization is a crucial factor influencing respondents' receiving C-section delivery.…”
Section: Discussionmentioning
confidence: 68%